Digoxin Enhances the Anticancer Effect on Non-Small Cell Lung Cancer While Reducing the Cardiotoxicity of Adriamycin - Wang, Yingying; Ma, Qian; Zhang, Shaolu; Liu, Hongyan; Zhao, Baoquan; Du, Bo; Wang, Wei; Lin, Peng; Zhang, Zhe; Zhong, Yuxu; Kong, Dexin (Frontiers in Pharmacology, 2020)
Digoxin is widely used to treat heart failure. Epidemiological studies suggested it might be used as an anticancer drug or sensitizing agent for cancer therapy. Adriamycin is a well-known anticancer drug, but often causes cardiotoxicity which limits its use. We recently investigated the anticancer effects of digoxin alone or in combination with adriamycin on human non-small cell lung cancer in vitro and in vivo. Digoxin reduced the viability of A549 and H1299 cells in vitro, increased DNA damage by promoting ROS generation and inhibiting both DNA double strand break (DSB) and single strand break (SSB) repair. Combination with adriamycin showed synergistic antiproliferative effects at the ratios of 1/2IC50DIG׃ IC50ADR and IC50DIG ׃ IC50ADR on A549 and H1299 cells, respectively. In vivo, digoxin potently inhibited A549 growth in both zebraﬁsh and nude mouse xenograft model. Co-treatment with adriamycin not only enhanced the antitumor efficacy, but also reduced the cardiotoxicity. Our findings suggest that digoxin has the potential to be applied as an antitumor drug via inhibiting both DNA DSB and SSB repair, and combination with adriamycin for therapy of human non-small cell lung cancer is reasonable.